Successful treatment of facial systemic lupus erythematosus lesions with Dr Michaels® (Soratinex®) product family. A case report - Tirant, M; Bayer, P; Hercogovấ, J; Fioranelli, M; Gianfaldoni, S; Chokoeva, A A; Tchernev, G; Wollina, U; Novotny, F; Roccia, M G; Maximov, G K; França, K; et al. (Journal of biological regulators and homeostatic agents, 2016)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease in which the bodys immune system mistakenly attacks healthy tissue. It can affect the skin, joints, kidneys, brain and other organs. We report the case of a 7-year-old female patient with facial lesions of SLE since the age of 5. There was no significant family history and patient had been a healthy child from birth. The child presented with a malar rash, also known as a butterfly rash, with distribution over the cheeks but sparing the nasal bridge. This case represents the efficacy of the Dr. Michaels® (Soratinex®) product family in the successful resolution of facial lesions of SLE.
Keywords: exantém; Lupus Erythematosus, Systemic; systémový lupus erythematodes; Child; lidé; Female; dítě; Exanthema; ženské pohlaví; Humans